Effect of season on the biochemical characteristics of donkey (Equus asinus) semen* - ROY, A K; YADAV, M P; SENGAR, O P S (The Indian Journal of Animal Sciences, 2014)
The biochemical characteristics of donkey semen were studied during summer, autumn and winter. The mean concentration of glucose in the seminal plasma was significantly higher (P<0.01) during autumn and winter than in summer. The cholesterol was significantly higher (P<0.01) in autumn as compared to summer. There was no significant difference in the total protein and albumin among different seasons. The activity of acid phosphatase was significantly more (P< 0.01) during autumn and winter than in summer, There were differences (P< 0.01) in the activities of alkaline phosphatase and lactate dehydrogenase among seasons. The activity of aspartate aminotransferase was more (P<0.01) in winter than in summer, The activity of alanine aminotransferase during winter was more (P< 0.01) than that of summer and autumn.